Status and Constraints of Backyard Poultry Farming in Mizoram - Rahman, Saidur (Indian Journal of Hill Farming, 2018)
Backyard Poultry farming is a traditional farming practice in Mizoram since time immemorial practiced by Mizo women. The study was carried out to analyze the status and constraints of backyard poultry production amongst the women in Aizawl and Mamit districts of Mizoram, India. A total of 200 women poultry rearers were selected from 10 villages. The study revealed that majority of the respondents were from middle age group, literate, housewives, possessed less than 1 hectare of land and belonged to BPL category, rearing coloured non-descript native birds. Local chickens were reared for dual purpose predominately under free range scavenging system by providing kitchen leftover, insect, worms, crop residues, grass and grains as feed materials. They got chicks by natural hatching at home and used bamboo made brooder for hatching the eggs. They did not practice vaccination and deworming of birds and mortality rate in birds due to Ranikhet disease was the highest, followed by fowl pox, greenish diarhhorea, respiratory problems etc. They sold eggs and birds directly to the consumers. The major constraints as revealed in the study were non-availability of improved chicks for rearing, predators and occurrence of diseases.